2010
DOI: 10.2320/matertrans.m2010056
|View full text |Cite
|
Sign up to set email alerts
|

Friction Coefficient in Hot Compression of Cylindrical Sample

Abstract: In order to analyze the evolution behavior of friction coefficients during large strain hot forging processes, compression tests were carried out on IHS38MSV hypoeutectoid steel samples at a stroke rate of 1.2 mm/s and temperatures ranging from 1073 to 1473 K. The simulation results of the geometrical change in the sample during the compression process obtained by using various friction coefficients were compared with experimental results in order to verify the validity of the ''instantaneous friction coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 7 publications
(7 reference statements)
0
35
0
2
Order By: Relevance
“…During compression processing, adiabatic heating and interfacial friction between the specimen and anvils have great influences on the mechanical responses of the materials [10]. However, in this study the effects of these two factors on the flow stress-strain curve in the Thermal/Mechanical Simulator were not considered.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…During compression processing, adiabatic heating and interfacial friction between the specimen and anvils have great influences on the mechanical responses of the materials [10]. However, in this study the effects of these two factors on the flow stress-strain curve in the Thermal/Mechanical Simulator were not considered.…”
Section: Introductionmentioning
confidence: 95%
“…Although graphite was used to lubricate the contacting surface, the friction coefficient at high temperatures cannot be lowered to a negligible level [10]. The friction corrected flow stress can be calculated using the following equations [25]:…”
Section: Friction and Temperature Corrected Approachmentioning
confidence: 99%
“…Previous research showed that the traditional correction of -" curves including both friction factor determination and friction correction potentially has a severe shortcoming, because the compressed sample was supposed to be very thin and it is assumed that there is no barreling in the edges of the sample, that is, the thickness is small enough and the average axial stress z is constant across the height of sample. 12,13) However, in an actual cylindrical hot working process, the thickness of sample is generally higher than the radius of a sample. The stress across the height of a sample is considered not to be constant.…”
Section: Resultsmentioning
confidence: 99%
“…The corrected stresses of sample can be calculated when the flow stress and friction factor, m are substituted into the following equation based on a previous research, 13)…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Split Hopkinson Pressure Bar experiments, it is important that stress equilibrium is reached inside the specimen: the sample should be sufficiently thin to obtain >3 internal reflections of the stress wave. The sample diameter should be both less than the diameter of the bars, and sufficiently small to ensure that any stresses due to radial inertia are negligible [1].…”
Section: Introductionmentioning
confidence: 99%